Fathers' involvement in their wives'/partners' breastfeeding: A qualitative study - Nur Intan Kusuma; Eka Budiarto; Rini Kristiyanti; Milatun Khanifah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Increasing the coverage of breastfeeding can improve survival and protect children from chronic diseases. However, the low coverage of exclusive breastfeeding is a problem caused by internal and external factors. One of the external factors is the lack of support from the husband. Purpose: To explore the involvement of husbands in the process of mothers providing exclusive breastfeeding to their babies. Method: Qualitative research with a generic qualitative approach. Participants in this study were breastfeeding mothers who had babies over six months old and had passed the period of exclusive breastfeeding. The number of breastfeeding mothers was 8 people with the principle of data saturation. The researcher was the main instrument in the study. Other instruments used were interview guidelines, field notes, and audio recorders. The interview results were analyzed thematically. Results: Frequency distribution data were obtained from unemployed mothers as many as 75% with the majority of high school education with an age range of 25-34 years. The results of the study showed that mothers' acceptance of husbands' involvement in the process of providing exclusive breastfeeding included emotional involvement and physical involvement. Conclusion: Mothers believe that husband's involvement is very important in the process of exclusive breastfeeding. The involvement received by mothers can be in the form of emotional involvement in the form of attention and informative advice and physical involvement as a form of practical support in the process of exclusive breastfeeding. Husbands who have sufficient information about exclusive breastfeeding and are aware of the importance of the health and development of babies will decide to be actively involved in the process of exclusive breastfeeding.